Striving for effective social development interventions in South Africa: A conceptual assessment of religion-state partnerships - Baron, Eugene; Solomons, TJ (Stellenbosch Theological Journal, 2024)
The socio-economic conditions of the poor in South Africa remain dire, and little has been done to improve them. However, many faith-based organizations (FBOs) have entered into agreements with the state to overcome various social development problems. Nevertheless, since questions continue to be raised regarding the rate of resolution of social development problems in South Africa, the difficulty may lie with the conceptualization and understanding of the partnership between church and state and the role that this partnership plays. This article reports on a critical assessment of the partnerships between FBOs in Elsies River and some Western Cape government organizations. The study entailed semi-structured interviews with a purposive sample to understand how both role players understood the FBO-state partnership, and how their understanding and social praxis either brought about more complexities and negative consequences or had a beneficial and positive influence on how poor social conditions in the communities are attended to. The study found that the South African government is not always adequately resourced to provide the necessary social welfare services and therefore makes use of alternative service providers to render social development services on its behalf. Furthermore, the study raises a deep concern about the imbalance in the power relations between the two stakeholders.